Meta-Analysis Problem Based Learning on Students' Problem-Solving Skills in Higher Education - Atmaja, Theodore Alexander; Santosa, Tomi Apra; Sakti, Bayu Purbha; Yustitia, Via; Kurniawan, Andri; Meriyati, Meriyati; Ali, Makhrus (eScience Humanity Journal, 2024)
This study aims to determine the influence of problem-based learning on the problem- solving ability of students in higher education. This type of research is a quantitative research with a meta-analysis approach. The sample of this study comes from the analysis of 12 national and international journals published in 2023-2024. The data source was taken from the Google Scholar, ERIC and Mendeley databases. The sampling technique is direct observation through a journal database. Data analysis is a quantitative analysis with the help of the STATA application. The results of this study show that there is a significant influence of the problem-based learning model on the problem-solving ability of students in higher education with ES = 1,014; z = 9.013 with a high effecrt size category. These findings show that the problem-based learning model is very effective in being applied by lecturers in the learning process in higher education